Chapter Gli economisti e il corporativismo nell'Italia fascista - Bini, Piero (Studi e saggi, 2021)
This paper focuses on the role and relevance of Corporatism in the Italian tradition of economic studies during the 1920s and 1930s. Historiography offers two different interpretations: Corporatism as a propaganda phenomenon and an economic doctrine limiting freedom; Corporatism as a series of policy measures devised to stabilize the Italian economy after WW1. To correctly assess the phenomenon of Corporatism, this paper chooses a different approach: an in depth analysis of the main theoretical answers proposed by Italian economists in regard to the most significant policy issues of the time. For example: corporatist wage and labor policy, the post-1929 relief measures, the bail out of some leading banks, the foundation of the Italian Financial Institute (IMI) in 1931 and of the Industrial Reconstruction Institute (IRI) in 1933, and finally the projected third way between a market economy and a command economy. One of the main conclusions of this research is that the energies and time spent into devising a Corporatist economic system and Corporatist policy measures hindered the advancement of economic studies in Italy.